O tempo no tempo: um estudo do desenvolvimento das durações a partir das primeiras palavras - Matos, Nuno (2017)
The study of duration patterns in early speech has yield contradictory results regarding the role played by biological factors and language specificity. We have examined the development of duration patterns in the speech of one European Portuguese child, from 1;04 to 2;04. Our findings show two different moments of temporal reorganization: the first related to PW duration; the second to syllable duration as a function of number of syllables in higher prosodic domains. The latter moment leads to the emergence of phrase-final lengthening. We interpret these findings as supporting the role played by the native language, and as providing evidence for the emergence of prosodic structure in language production.